2021
DOI: 10.3390/cells10113134
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in the Interconversion, Turnover and Degradation of Chlorophyll

Abstract: Chlorophylls (Chls, Chl a and Chl b) are tetrapyrrole molecules essential for photosynthetic light harvesting and energy transduction in plants. Once formed, Chls are noncovalently bound to photosynthetic proteins on the thylakoid membrane. In contrast, they are dismantled from photosystems in response to environmental changes or developmental processes; thus, they undergo interconversion, turnover, and degradation. In the last twenty years, fruitful research progress has been achieved on these Chl metabolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 95 publications
1
27
1
Order By: Relevance
“…Compared with wild type embryos, most genes involved in photosystem I ( OsPSA s), photosystem II ( OsPSB s), and light-harvesting complex ( OsLHCAs and OsLHCBs ) (Ben-Shem et al, 2003 ; Gao et al, 2018 ) were synergistically upregulated in Oslec1-1 embryos ( Figure 5A ). In addition, several DEGs involved in chloroplast development, as well as chlorophyll biosynthesis and degradation (Bollivar, 2006 ; Hu et al, 2021 ) were also upregulated, such as OsSGRL, OsPORA, OsPORB , and OsNYC4 ( Figure 5A ). Chloroplast biosynthesis genes are in the majority, and the OsPORA with the largest increase is chloroplast biosynthesis related.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with wild type embryos, most genes involved in photosystem I ( OsPSA s), photosystem II ( OsPSB s), and light-harvesting complex ( OsLHCAs and OsLHCBs ) (Ben-Shem et al, 2003 ; Gao et al, 2018 ) were synergistically upregulated in Oslec1-1 embryos ( Figure 5A ). In addition, several DEGs involved in chloroplast development, as well as chlorophyll biosynthesis and degradation (Bollivar, 2006 ; Hu et al, 2021 ) were also upregulated, such as OsSGRL, OsPORA, OsPORB , and OsNYC4 ( Figure 5A ). Chloroplast biosynthesis genes are in the majority, and the OsPORA with the largest increase is chloroplast biosynthesis related.…”
Section: Resultsmentioning
confidence: 99%
“…The lipid group of the chloroplast membrane is unique and mainly consists of uncharged monogalactosyl diacylglycerol (MGDG) and digalactosyl diacylglycerol (DGDG) [ 26 , 27 ]. It has been shown that when MGDG is lacking, the membrane energetics and photoprotection are impaired [ 28 ]; whereas the deficiency of DGDG leads to the dissociation of extrinsic proteins of the photosystem II (PSII) reaction center complex [ 29 ]. The photosynthetic electron transport chain is located in the vesicle-like membrane and consists of photosystem II (PSII), cytochrome (Cytb6f), photosystem I (PSI), plastid quinone (PQ) and plastid cyanidin (Pc) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments, the increase in Chl contents detected in all the shaded species demonstrated the dynamic ability of plants to maximize the light-harvesting capacity in low light. On the other hand, the lower Chl contents detected in the sun-adapted tree leaves is likely aimed to prevent possible photoinhibition of photosynthesis under excessive light, especially around midday (Jason et al 2004;Dai et al 2009;Hu et al 2021).…”
Section: Light Quantity and Quality Influenced The Leaf Pigment Contentmentioning
confidence: 99%